Conservation status and reintroduction of the Cocos Buff-banded Rail, Gallirallus philippensis andrewsi. (1st March 2016) - Woinarski, J. C. Z.; Macrae, I.; Flores, T.; Detto, T.; Reid, J.; Pink, C.; Flakus, S.; Misso, M.; Hamilton, N.; Palmer, R.; Morris, K.; Znidersic, L.; et al.
Abstract: An endemic subspecies of Buff-banded Rail ( Gallirallus philippensis ) is restricted to the Cocos (Keeling) Islands, a group of 27 islands, with total area of 15 km 2, in the north-eastern Indian Ocean. Human settlement led to marked environmental degradation of the 26 islands in the southern atoll of the group. The Cocos Buff-banded Rail declined severely, with the last confirmed record from islands in the southern atoll in 1991. The subspecies has persisted, however, with a population of 800 individuals, on a single island, Pulu Keeling, 24 km north of the southern atoll. A recovery plan for this endangered subspecies recommended reintroduction to a suitable island in the southern atoll. This paper provides a brief overview of the history and status of the subspecies, and describes an April 2013 reintroduction of 39 rails from Pulu Keeling to the 1-km 2 Horsburgh Island in the southern atoll. This program has had at least short-term success, with monitoring showing successful recruitment in the reintroduced population, and its increase to 54 individuals by October 2014 and 121 individuals by June 2015. Much of the world's loss of biodiversity has been from, and continues to occur on, islands: this project demonstrates that well-considered mitigation of threats and translocation programs can provide solutions to this challenge.